A Norwegian cohort with STAT1-related disease – further expanding the clinical phenotype - Martinsen, Karen Helene Bronken; Øverland, Torstein; Stray-Pedersen, Asbjørg; Abrahamsen, Tore G.; Fevang, Børre; Landsverk, Hans Christian Erichsen (Frontiers in Immunology, 2025)
PurposeInborn errors of immunity (IEIs) caused by mutations in STAT1 are associated with a broad range of clinical manifestations, ranging from relatively mild to life-threatening. Our aim was to give a clinical and molecular description of a Norwegian cohort with STAT1-related disease.MethodsThis is a descriptive epidemiological study.ResultsWe present 23 patients with heterozygous STAT1 mutations, from 12 unrelated Norwegian families. Eighteen individuals had STAT1 gain-of-function (GOF) variants. Chronic mucocutaneous candidiasis (CMC) was the most common manifestation, observed in 94% of patients. Herpesviruses caused morbidity in one-third of patients, with severe complications such as varicella meningitis, varicella retinitis and ulcerative CMV esophagitis seen in 17%. Autoimmune hypertriglyceridemia with GPIHBP1 autoantibodies was diagnosed in one patient, adding a new entity to STAT1 GOF. Fifty percent of patients suffered chronic ophthalmologic manifestations. Severe gastrointestinal manifestations were observed in 22% of patients. Five of the 23 patients had STAT1 loss-of-function (LOF) variants. Mendelian susceptibility to mycobacterial disease (MSMD) was detected in three patients. Malignancy and autoimmunity were observed in two patients, both were heterozygous for the p.Ala246Thr variant, which is likely associated with a more complex phenotype. Significant viral infections were also observed. Presently, our cohort represents the largest nationwide study on STAT1-related disease.ConclusionWe report novel clinical manifestations in STAT1 GOF, and suggest that heterozygous STAT1 LOF might be a more complex condition than originally presumed.